Evaluación del conocimiento de los cirujanos dentistas brasileños sobre aspectos bioéticos en el tratamiento odontológico - Gonçalves, P. E. [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Oliveira, R. N. de (SciELO Espana/Repisalud, 2007)
Professional-patient relationship and its importance for a good performance and success of the dental treatment must be reflected upon by means of their bioethical aspects. Our study aimed at evaluating dentist-surgeons' knowledge (n=163) in conducting specialization courses at São Paulo State University-UNESP, on these aspects. Out of the people surveyed, 88.1% mentioned that a decision for the treatment should be made by mutual agreement between professionals and patients, however, 26.4% report that patients' or their legal representative's participation in decision-making can cause negative interference. Professionals' acting when patients choose a less suitable treatment, 95.6% try to convince patients that it is not the best choice and persuade them for a better one by keeping the paternalistic model. It was noticed that 20.3% did not know how to relate the importance of professional-patient interaction as regards the dental treatment. It was therefore concluded that many dentist-surgeons are not taking these bioethical aspects into account in clinical practice.
Evaluation of the knowledge of Brazilian dental surgeons on bioethical aspects of dental treatment
Keywords: Bioethics; Paternalism; Personal autonomy; Professional-patient relation